Differentiation-dependent susceptibility of human muscle cells to Zika virus infection. - Vincent Legros; Patricia Jeannin; Julien Burlaud-Gaillard; Thibault Chaze; Quentin Giai Gianetto; Gillian Butler-Browne; Vincent Mouly; Jim Zoladek; Philippe V Afonso; Mariela-Natacha Gonzàlez; Mariette Matondo; Ingo Riederer; et al. (Public Library of Science (PLoS), 2020)
Muscle cells are potential targets of many arboviruses, such as Ross River, Dengue, Sindbis, and chikungunya viruses, that may be involved in the physiopathological course of the infection. During the recent outbreak of Zika virus (ZIKV), myalgia was one of the most frequently reported symptoms. We investigated the susceptibility of human muscle cells to ZIKV infection. Using an in vitro model of human primary myoblasts that can be differentiated into myotubes, we found that myoblasts can be productively infected by ZIKV. In contrast, myotubes were shown to be resistant to ZIKV infection, suggesting a differentiation-dependent susceptibility. Infection was accompanied by a caspase-independent cytopathic effect, associated with paraptosis-like cytoplasmic vacuolization. Proteomic profiling was performed 24h and 48h post-infection in cells infected with two different isolates. Proteome changes indicate that ZIKV infection induces an upregulation of proteins involved in the activation of the Interferon type I pathway, and a downregulation of protein synthesis. This work constitutes the first observation of primary human muscle cells susceptibility to ZIKV infection, and differentiation-dependent restriction of infection from myoblasts to myotubes. Since myoblasts constitute the reservoir of stem cells involved in reparation/regeneration in muscle tissue, the infection of muscle cells and the viral-induced alterations observed here could have consequences in ZIKV infection pathogenesis.